The Socio-Economic Dynamics of Communities in Sungai Aur District, West Pasaman Regency - Aulia Rahmi Putri; Azmi Fitrisia; Paus Iskarni; Fadilla Syahriani (UIN Imam Bonjol Padang, 2025)
The aim of this research is to analyze the socioeconomic dynamics of the community in Sungai Aur District, West Pasaman Regency, from a historical perspective. A qualitative research method was employed, utilizing interviews, observation and documentation. The findings indicate that in the initial stages of the transmigration program, the community received agricultural land for cultivation to improve economic well-being. However, many residents planted oil palm without adequate knowledge, influenced by the economic success of surrounding areas. Recognizing the geographical unsuitability, some community leaders encouraged the cultivation of more appropriate crops like coffee. Conversely, a portion of the community chose to sell their land to newcomers, thereby losing their primary assets and transitioning to agricultural laborers. This highlights the importance of land management strategies and human resource capacity building in supporting the success of transmigration programs.